2000
DOI: 10.1097/00000539-200003000-00029
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Intravenous 0.15 Versus 0.25 mg/kg Intraoperative Morphine for Immediate Postoperative Analgesia After Remifentanil-Based Anesthesia for Major Surgery

Abstract: The administration of 0.15 or 0.25 mg/kg perioperative morphine during remifentanil-based anesthesia for major surgery does not preclude additional morphine administration in the postanesthesia care unit. The larger dose of 0.25 mg/kg slightly improves postoperative analgesia; however, it may be responsible for postoperative respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 14 publications
0
21
0
2
Order By: Relevance
“…In the present study, remifentanil infusion was started at 0.05 μg/kg per minute initially and then adjusted between 0 and 0.1 μg/ kg per minute based on patient responses, which were chosen from previous studies of monitored anesthesia care [13,14]. Although remifentanil-based intraoperative analgesia has been associated with increased postoperative analgesic requirements [15,16], we did not see this situation in this study. This difference may be due to the unique pain characteristics of hysteroscopy.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, remifentanil infusion was started at 0.05 μg/kg per minute initially and then adjusted between 0 and 0.1 μg/ kg per minute based on patient responses, which were chosen from previous studies of monitored anesthesia care [13,14]. Although remifentanil-based intraoperative analgesia has been associated with increased postoperative analgesic requirements [15,16], we did not see this situation in this study. This difference may be due to the unique pain characteristics of hysteroscopy.…”
Section: Discussionmentioning
confidence: 97%
“…During intra-abdominal surgery, several authors have suggested to maintain an infusion rate of 0.5 mg kg À1 .min À1 (corresponding to a concentration around 15 ng ml À1 ) to block any response to surgical stimuli (24)(25)(26) but this may lead to hypotension (27) or severe bradycardia (24). A pharmacodynamic modelling performed by Drover and colleagues estimated the remifentanil EC 50 to block response between 5 and 7 ng ml À1 , and the EC 95 just above (21).…”
Section: Intraoperative Haemodynamic Stabilitymentioning
confidence: 99%
“…However, this protocol presents problems, such as delayed recovery and postoperative respiratory depression [16, 17]. Haemodynamic instability is frequently encountered during emergence from remifentanil-based anaesthesia [18].…”
Section: Resultsmentioning
confidence: 99%